'Mine's a Pint of Bitter': Performativity, gender, class and representations of authenticity in real-ale tourism. (December 2013) - Spracklen, Karl; Laurencic, Jon; Kenyon, Alex
Leisure choices are expressive of individual agency around the maintenance of taste, boundaries, identity and community. This research article is part of a wider project designed to assess the social and cultural value of real-ale to tourism in the north of England. This article explores the performativity of real-ale tourism and debates about belonging in northern English real-ale communities. The research combines an ethnographic case study of a real-ale festival with semi-structured interviews with organisers and volunteers, northern English real-ale brewers and real-ale tourists visiting the festival. It is argued that real-ale tourism, despite its origins in the logic of capitalism, becomes a space where people can perform Habermasian, communicative leisure, and despite the contradictions of preferring some capitalist industries over others on the basis of their perceived smaller size and older age, real-ale fans demonstrate agency in their performativity.